Implementation Of Presidential Regulation Number 98 Of 2020 On Salaries And Allowances Of Pppk Unpaid By The City Government Of Bandar Lampung - Kalandoro, M. Raihan; Rompies, Adrian E; Nurzaman, R Adi (Universitas Muhammadiyah Sumatera Utara, 2024)
State Civil Apparatus or ASN is a profession for Civil Servants (PNS) and Government Employees with Employment Agreements (PPPK) who work in central and regional government agencies. PPPK are Indonesian citizens who meet certain requirements, who are appointed based on a work agreement for a certain period of time in order to carry out government duties. Every ASN employee has the right to receive awards and recognition in the form of material or non-material. One of the components of appreciation and recognition for ASN employees is income consisting of salary and wages. PPPK salary is compensation in the form of money which the government must pay fairly and appropriately to PPPK in accordance with the workload, responsibilities and risks of the job. In implementing Presidential Regulation Number 98 of 2020, the Bandar Lampung City Government has prepared a personnel expenditure budget plan which is prepared based on the total APBD of the Bandar Lampung City Government. These employee expenditures are used to pay salaries and also additional income for ASN employees, both PPPK and PNS. PPPK has the right to receive salaries and allowances provided by related agencies, as stated in Presidential Regulation Number 98 of 2020 concerning PPPK salaries and allowances. Meanwhile, legal action that can be taken is by conducting mediation with the relevant agencies, but if no agreement is found, you can report it through the relevant agency or commission where the PPPK is affiliated